Brand loyalty analysis of stie Indonesia banking school students - Undang Sundara (Institute of Accounting Research and Novation (IARN), 2021)
This research is being conducted to find out the level of loyalty of the students of the Indonesia Banking School (IBS) Jakarta in every level of brand loyalty dimension. This research was also conducted in order to find out whether there were differences in loyalty levels between junior students (class of 2007 and 2008) and senior students (class of 2004, 2005 and 2006) or not. Based on this research, there are some results that can be concluded. In the switcher dimension, students of IBS are included in the high loyalty category with the score of 3.67 (range 3.401 – 4.200). In the habitual buyer dimension, students are included in the low category with a score of 2.09 (range 1.801 – 2.600). In the satisfied buyer dimension, the students are included in the medium category with a score of 3.21 (range 2.601 – 3.400). In likes the brand dimension, the students have an average score of 3,400 and are included in the medium category (range 2,601 – 3,400). In the committed buyer dimension, students of IBS are included in the medium category with the average score of 3.09 (range 2.601 – 3.400). The test of hypothesis shows that in both brand loyalty as a whole and it's detailed analysis of every dimension, there is no significant difference in loyalty level in junior and senior students in IBS. This statement can be proven with the independent sample T-test output, which has a bigger score in the significant score rather than it's alpha (0.05). The test of hypothesis shows that in both brand loyalty as a whole and it's detailed analysis of every dimension, there is no significant difference in loyalty level in junior and senior students in IBS. This statement can be proven with the independent sample T-test output, which has a bigger score in the significant score rather than it's alpha (0.05). The test of hypothesis shows that in both brand loyalty as a whole and it's detailed analysis of every dimension, there is no significant difference in loyalty level in junior and senior students in IBS. This statement can be proven with the independent sample T-test output, which has a bigger score in the significant score rather than it's alpha (0.05).